A simple electrochemical methodology for evaluation of the velocity of electroosmotic flow at the tip of polarized microcapillary. (20th February 2015) - Silver, Barry R.; Holub, Karel; Mareček, Vladimír
Abstract: A simple electrochemical methodology for evaluation of the velocity of electroosmotic flow at the tip of a polarized microcapillary is herein described. The methodology relies on the application of a composite, potentiostatically-controlled voltage signal which comprises both AC and DC polarization components. Subsequent analysis of the current-time response yields an approximation for the velocity of electroosmotic flow at the microcapillary tip. Using this methodology, it is also herein shown, that previously observed low-frequency pseudo-inductive behaviour is related to an accumulation of ions into the capillary tip region under an applied potential via a mechanism based on electroosmosis.